CSR during COVID-19 Pandemic and Mapping with Schedule VII of Companies Act, 2013 vis-à-vis SDGs: Reflections from BSE Manufacturing Index Companies (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The article tries to shed some light on the  Corporate Social Responsibility (CSR) activities  undertaken by the top Indian manufacturing  companies to combat the social, economic  and health challenges emanated from the  COVID-19 crisis. Effort was also made to  map the CSR activities undertaken during this  pandemic situation with the mandated list of  CSR activities under Schedule VII of Companies  Act, 2013 and Sustainable Development  Goals (SDGs) in general using Content  analysis technique. The outcome of the study  revealed that majority of the selected Indian  manufacturing companies have undertaken  various preventive and mitigation measures for  enabling the stakeholders to tide over the crisis  which can be mapped with Clauses i, v and ix  of Schedule VII of Companies Act, 2013 and  SDGs 2, 3, 8 and 17.
Keywords: CSR; COVID-19; SDGs; Companies Act; 2013; Content Analysis